The perils of technocratic power: Central bank discretion and the end of bretton woods revisited - Aditi Sahasrabuddhe; Jack Seddon (Queen's University Centre for Economic History (QUCEH), 2025)
Recent crises have cast doubt on the legitimacy of technocratic power, yet its role in global economic governance remains poorly understood. Revisiting the collapse of Bretton Woods, we propose a dynamic theory of global monetary governance to explain how expanding central bank discretion can destabilize systems. While most studies attribute the postwar system's failure to geopolitical struggles, institutional weaknesses, or shifting economic ideas, they overlook the policies designed to manage and stabilize it. Drawing on historical institutionalism, we show how coordination tensions between rule-bound and discretionary policymakers-and the mutually reinforcing adaptation risks they faced-produced responses that appeared stabilizing in the short term but ultimately eroded long-run stability. New archival evidence from the IMF, BIS, and OECD reveals how tools like the London Gold Pool and currency swap lines extended central bank power, concealed macroeconomic imbalances, and crowded out political momentum for structural reform. As technocratic authority grew misaligned with political support and functional economic adjustment, it became a liability. This challenges the dominant view that technocratic actors are inherently superior in managing global economic policy
Keywords: E42; E58; F33; N10; N14; N20; 330; Bretton Woods; London Gold Pool; monetary history; monetary governance; historical institutionalism